Compactness of Fuzzy Sets - Amani E. Kadhm (Journal of Madenat Alelem University College, 2011)
The objective of this paper is to study the compactness of fuzzy sets in fuzzy topological spaces, especially the connection between compact, closed and bounded fuzzy sets.